214k views
0 votes
2y + 7x = -5

5y - 7x = 12

x =

y =​

User DeltaTango
by
5.1k points

1 Answer

5 votes

Answer:

x = - 1, y = 1

Explanation:

Given the 2 equations

2y + 7x = - 5 → (1)

5y - 7x = 12 → (2)

Adding the2 equations term by term will eliminate the term in x, that is

7y = 7 ( divide both sides by 7 )

y = 1

Substitute y = 1 into either of the 2 equationsand solve for x

Substituting into (1)

2(1) + 7x = - 5

2 + 7x = - 5 ( subtract 2 from both sides )

7x = - 7 ( divide both sides by 7 )

x = - 1

solution is x = - 1, y = 1

User Rmooney
by
5.3k points